Neonatal upper limb fractures - a narrative overview of the literature - Marcos Carvalho; Maria Inês Barreto; João Cabral; Inês Balacó; Cristina Alves (BMC, 2024)
Abstract The aim of this paper is to review the topic of neonatal fractures of the upper limb, describing the different types of fractures focusing on the etiology, epidemiology, risk factors, clinical approach, diagnosis, treatment and prognosis of these injuries. We included all types of research studies, both experimental and observational, published in English, French, Portuguese and Spanish. The information was obtained using the keywords neonatal upper limb fracture, clavicle fracture or humerus fracture from the following resources: MEDLINE database, Embase® database and LILACS database. Other resources such as hand searches of the references of retrieved literature and authoritative texts, personal and hospital libraries searching for texts on upper limb neonatal fractures, discussions with experts in the field of upper limb neonatal fractures and personal experience, were also considered for the completion of the article. Neonatal fractures of the upper limb are consensually considered to have a good prognosis and no long-term sequelae. Conservative treatment is the option in the vast majority of the fractures and is associated with excellent results, with good healing, full range of motion, adequate remodeling without obvious deformity, neurologic impairment or functional implications.